The Influence of Entrepreneurial Knowledge and Social Media on Entrepreneurial Interest of Management Study Program Students at Universitas Wahid Hasyim - Refina Yulia Pancawati; Muhammad Ulin Nuha (International Journal of Management, Business, and Social Sciences, 2026)
This study aims to analyze the influence of entrepreneurial knowledge and social media on the entrepreneurial interest of students of the Management Study Program, Wahid Hasyim University, Semarang. The background of this research is driven by the high unemployment rate among university graduates, which demands an increase in entrepreneurial spirit as an alternative solution in creating jobs. This study uses a quantitative approach with data collection techniques through questionnaires distributed to 75 student respondents of the class of 2021. Data analysis was carried out using SPSS version 26 with validity, reliability, classical assumption test, multiple linear regression test, t test, F test, and determination test. The results showed that entrepreneurial knowledge had a positive and significant effect on entrepreneurial interest (t-count 4.772 > t-table 1.666; sig. 0.000 < 0.05), as well as social media (t-count 4.543 > t-table 1.666; sig. 0.000 < 0.05). Simultaneously, these two variables have an influence on significant to students' entrepreneurial interest (F-count 88.168; sig. 0.000). Thus, it can be concluded that entrepreneurial knowledge and the use of social media together contribute to increasing students' interest in becoming entrepreneurs. This research provides important implications for higher education institutions to further strengthen the entrepreneurship curriculum and encourage the use of digital media in supporting the entrepreneurial spirit of students.